US a narrative history a narrative history a narrative history - Davidson, James West. (McGraw-Hill, 2009)
The first civilizations of North America; Old worlds, new worlds [1400-1600]; Colonization and conflict in the South [1600-1750]; Colonization and conflict in the North [1600-1700]; The Mosaic of eighteeth-century America [1689-1771]...